Unwinding of the C‐Terminal Residues of Neuropeptide Y is critical for Y2 Receptor Binding and Activation1. Issue 25 (29th April 2015) - Kaiser, Anette; Müller, Paul; Zellmann, Tristan; Scheidt, Holger A.; Thomas, Lars; Bosse, Mathias; Meier, Rene; Meiler, Jens; Huster, Daniel; Beck‐Sickinger, Annette G.; Schmidt, Peter
Abstract Despite recent breakthroughs in the structural characterization of G‐protein‐coupled receptors (GPCRs), there is only sparse data on how GPCRs recognize larger peptide ligands. NMR spectroscopy, molecular modeling, and double‐cycle mutagenesis studies were integrated to obtain a structural model of the peptide hormone neuropeptide Y (NPY) bound to its human G‐protein‐coupled Y2 receptor (Y2R). Solid‐state NMR measurements of specific isotope‐labeled NPY in complex with in vitro folded Y2R reconstituted into phospholipid bicelles provided the bioactive structure of the peptide. Guided by solution NMR experiments, it could be shown that the ligand is tethered to the second extracellular loop by hydrophobic contacts. The C‐terminal α‐helix of NPY, which is formed in a membrane environment in the absence of the receptor, is unwound starting at T32 to provide optimal contacts in a deep binding pocket within the transmembrane bundle of the Y2R.